2007
DOI: 10.1016/j.visres.2007.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkeys mislocalize saccade targets flashed for 100ms around the time of a saccade

Abstract: Humans and monkeys mislocalize targets flashed around the time of a saccade. Here, we present data from three monkeys on a double-step task with a 100ms target duration. All three subjects mislocalized targets that were flashed around the time of the first saccade, in spite of long intersaccadic intervals. The error was consistently in the direction opposite that of the saccade, and occurred in some cases when the target presentation was entirely presaccadic. This is inconsistent with a theory invoking a dampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
(80 reference statements)
2
27
2
Order By: Relevance
“…Changes in RFs are likely to warp visual space during saccades. Psychophysical studies in monkeys have suggested that RF shifts/ expansions may underlie saccadic mislocalization [6]. Human studies are consistent with findings on remapping in monkeys (see [7] for review).…”
Section: Temporal and Spatial Aspects Of Remappingsupporting
confidence: 65%
“…Changes in RFs are likely to warp visual space during saccades. Psychophysical studies in monkeys have suggested that RF shifts/ expansions may underlie saccadic mislocalization [6]. Human studies are consistent with findings on remapping in monkeys (see [7] for review).…”
Section: Temporal and Spatial Aspects Of Remappingsupporting
confidence: 65%
“…11 L). In a monkey study, Jeffries et al (2007) found almost no significant positive mislocalization presaccadically but a strong negative mislocalization after saccade onset. In their paper, they argued that this finding is inconsistent with a theory of a dampened eye position signal.…”
Section: Parameter Variationsmentioning
confidence: 88%
“…The perisaccadic shift also depends on flash duration (Jeffries et al, 2007;Van Wetter and Van Opstal, 2008). The main effect in the experimental data of Van Wetter and Van Opstal (2008) is that the localization error diminishes for longerlasting stimuli right at saccade onset (Fig.…”
Section: Flash Length Dependencymentioning
confidence: 90%
“…Since little actual movement of the extraocular muscles took place, it is unclear why a largely stable retinal image should contradict the inflow signal and lead to perceived external motion. In addition, certain localization errors have been found to arise just prior to a saccade, before the eyes actually begin to move (e.g., Jeffries, Kusunoki, Bisley, Cohen, & Goldberg, 2007;see Ross, Morrone, Goldberg, & Burr, 2001 for a relevant review). This may suggest a slight temporal misalignment of corollary discharge with actual eye position (Honda, 1995;Matin, Matin, & Pearce, 1969;.…”
Section: Displacement Suppressionmentioning
confidence: 99%